EVALUATION OF POTATO GENOTYPES FOR KEEPING QUALITY UNDER AMBIENT CONDITIONS IN NEPAL - Gautam, I P; Khatri, B B; Sharma, M D; Thapa, R B; Shrestha, K; Chaudhary, D (Potato Journal, 2013)
An experiment on keeping quality of potato under non-refrigerated storage conditions was conducted during 2011 for 120 days under dark room at ambient temperature (25.8 Â± 1.2Â°C) and relative humidity (86.1%) to study the performance of seven potato genotypes for good storability. The results revealed that the genotypes BSU-PO3, HPS-II/67, PRP 25861.1 and Kufri Chipsona-2 were found suitable only for 45 to 60 days storage, while the genotypes Yagana and L-235.4 could be successfully stored for maximum period up to 120 days with minimum weight loss. The genotypes PRP 25861.1 and BSUPO3 had higher dry matter percentage and were found superior for processing in to chips.